Person Job Fit, Job Embeddedness dan Self Efficacy Terhadap Organizational Citizenship Behavior dengan mediasi Organizational Commitment - Zahra, Laela May Az; Suciningtyas, Santi; Masrokhah, Siti; Ningsih, Diah Wuriah (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
This study aims to analyze the influence of Person Job Fit, Job Embeddedness, and Self Efficacy on Organizational Citizenship Behavior with Organizational Commitment as a mediating variable among employees of the Social Affairs Office of Population Control, Family Planning, Women, and Children of Pemalang Regency. The sample collection used a census method with 66 respondents. The results of the multiple linear regression analysis showed a positive effect of Person Job Fit on Organizational Citizenship Behavior, a positive effect of Job Embeddedness on Organizational Citizenship Behavior, a positive effect of Self Efficacy on Organizational Citizenship Behavior, and a positive effect of Organizational Commitment on Organizational Citizenship Behavior. The t-test results indicated that Person Job Fit, Job Embeddedness, and Self-Efficacy have a significant influence on Organizational Citizenship Behavior. Additionally, the Sobel test results showed that Person Job Fit, Job Embeddedness, and Self Efficacy significantly influence Organizational Citizenship Behavior through Organizational Commitment.